LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING BAGI PESERTA DIDIK YANG BERPERILAKU AGRESIF DI SMP YAYASAN ATIKAN SUNDA BANDUNG - Amir Hidayat; Heris Hendriana; Muhamad Rezza Septian (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The problem of aggressive behavior by 16% to Junior High School students at school, especially in 8th graders of SMP Yayasan Atikan Sunda Bandung. This research aims to determine the implementation and responses of guidance and counseling teachers and students, as well as the obstacles which is found when implementing group guidance service using role playing technique. The method in this research uses descriptive method with a qualitative approach. Subject of the research are four respondent. Method of research used some technical of observation, interview and documentation. The results of the research shows that group guidance service with role playing technique was effective and significant for students who behave aggressively.The responses of students who had completed the group guidance service with role playing technique are they were excited and motivated to increase knowledge and raise self-confidence. Moreover, there were some behavior transformation after participating in group guidance service with this role playing technique.Keywords: : Role Playing Techniques, Aggressiveness, Group Guidance Service